Transformation of the Carboxyl Group of an Amino Acid to Variously Substituted Imidazoles through a Davidson-Type Heterocyclization - Küppers, Jim; Hympánová, Michaela; Keuler, Tim; Schneider, Andreas J.; Schnakenburg, Gregor; Gütschow, Michael (Synthesis, 2019)
The modification of amino acids leads to valuable building blocks for the synthesis of bioactive compounds. By keeping the amino group protected, the carboxylic acid functionality can be converted in two steps into an imidazole moiety via a Davidson-like heterocyclization. This reaction allows for a combinatorial approach, in which two positions at the heterocycle can be modified. Herein, we report the synthesis of such imidazole derivatives by employing N-protected cyclohexylalanine as the starting material. Different α-halo ketones were used and two points of diversity, positions 4 and 5, were examined. The structure of the final imidazole derivatives was confirmed by three X-ray crystal structure analyses and their protease inhibiting activities were evaluated.
Keywords: amino acids; Davidson synthesis; heterocycles; imidazoles; X-ray crystal structure analysis